(untitled) (Journal of human and social sciences, 2023)
The growing understanding of the importance of sustainable development as a necessity to achieve a balance between the needs of the present and the necessities of the future has made it a humanitarian priority. No national or international policy can be developed without making sustainable development its basis. International law has laid a groundwork to preserve humanity’s right to sustainable development. The human right to sustainable development requires individual and collective states to engage diligently, based on goodwill, in implementing commitments, fostering genuine cooperation, and exchanging experiences. This study aims to shed light on sustainable development in international law, both in terms of its historical evolution and the legal measures adopted to establish the right to sustainable development in international law. Keywords: Sustainable Development, Stockholm Declaration, Rio Declaration, Johannesburg Declaration, World Summit on Sustainable Development, United Nations Organization.